PENGUATAN RANCANGAN GOOD UNIVERSITY GOVERNANCE DALAM PENCEGAHAN KORUPSI DI PERGURUAN TINGGI - Alika Faza Qinthara (Fakultas Hukum Universitas Trunojoyo Madura, 2023)
This study aims to analyze the design of good university governance in preventing corruption at the tertiary level and the role of the internal control unit and the university senate in supervising higher education governance. This research is motivated by the rampant acts of corruption committed by officials in the world of education in Indonesia, especially in tertiary institutions. Corruptors in the world of education take advantage of loopholes to commit acts of corruption in various ways, one of which is through goods and services procurement project funds. The research methodology used is a normative juridical method with a statutory approach, a case approach, and a conceptual approach. The novelty in this research is to complement studies conducted by previous studies which only affect student trust and influence in positive terms, without preventing acts of corruption that are often carried out by officeholders in tertiary institutions. The results of the research show that good university governance can help prevent corruption if all the principles of good university governance are implemented or implemented in universities.